Analisis Perkembangan Likuiditas dan Rentabilitas pada BMT Beringharjo Yogyakarta Tahun 2005-2009 - Ahmad Ubaidillah; Khozainul Ulum (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Abstract: BMT Beringharjo Yogyakarta in its operations carried out a separation between the al mal and bait at-tamwil bait so that the financial statements of the two are separated from each other. This separation is intended to prevent the mixing of the two funds, considering that in the Bait at Tamwil is a community fund that is not intended to generate profits. While bait at tamwil has a clear orientation, namely to benefit from transactions for products issued by BMT. In this case, this research views BMT as a profit-oriented business institution, so the analyzed financial statements are bait-tamwil financial statements. The financial statements analyzed are related to the liquidity and profitability of BMT Beringharjo Yogyakarta. In facing business competition, every company or BMT needs to have good management skills to be able to continue to continue their business. One important thing that BMT needs to consider is the balance between liquidity and profitability. Therefore, author is interested in analyzing the development of the BMT Beringharjo financial performance. In this study, the discussion specializes in conditions of liquidity and profitability because these two factors are the main factors that financial analysts or customers want to know about. The purpose of this research is to explain how the development of Beringharjo BMT's liquidity and profitability over five years, from 2005 to 2009.This research is a field research. Data collection using interviews, observation and documentation or financial reports. Analysis of the data used is ratio analysis to determine liquidity and profitability conditions and trend analysis to determine the development of the two conditions for five years. The results showed that the liquidity condition of BMT Beringharjo Yogyakarta is not in a good condition because on average each year the figure was too small at 61.09% below 71%, it is reinforced by the trend line that continued to decline. The average profitability ratio per year of total assets is 9.69%. A figure of that size according to PINBUK is a figure that is too low but it is due to its profitability ratio which tends to fluctuate so that the difference in the ratio rate every year is so striking. In general, the condition of profitability is predicted with an upward trend line (positive trend). The condition of the ratio of earnings to total capital in BMT Beringharjo shows symptoms of improving from year to year. This can be seen on the trend graph that continues to rise, and the estimated value is positive. The average total earnings ratio of capital is 55.77% per year. A ratio of that size is an excellent figure for profit as indicated by a score of 4, which is at the level> 25%. Keywords: liquidity, rentability, BMT Beringharjo